Weingarten surfaces in three-dimensional product geometries - Vitti, Mannaim Gennaro (2025)
In this work, we seek to obtain information about certain types of Weingarten surfaces, approaching this problem through nonlinear partial differential equations. We study particular cases of translation surfaces in the product spaces H2xR and H3 and Helical surfaces in S2xR that verify the property of being a Weingarten Surface. In addition, we also investigate translation surfaces in the Euclidean space E3 that are particular cases of Weingarten Flow Solitons.